Binary mixture of the decanter cake and fiber from the oil palm industry waste as a solid fuel - Mohd Husin, Mohd Haizal; Ting, Sze Choi; Mohd Ruzmi, Nur Haziqah; Mohamad, Imran Syakir (2015)
This study relates to the production of solid fuel using waste products from the palm oil processing industry. Enclosed, the purpose of the study was to produce solid fuel from a binary mixture of decanter cake with the palm fiber. The sample was created based on decanter cake: fiber ratio, weight of loading and type of fiber. The sample were shaped into hexagons (radius= 2.34cm and length 8.0 cm). The sample was undergo moisture test, compression test and bomb calorimeter test. The study found out that the best mixture ratio among all of the sample ratio were 70% decanter cake and 30% fiber. The DC:F ratio of 70:30 has the highest compression force (2016 N) and nearest calorific value (4508 cal/g) compared to the commercial solid fuel which the compression force was 2390 N and calorific was 5321 cal/g.